(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
In this article I am going to share my knowledge on using “icebreaker” technique that I use in my classes. We can think of an icebreaker as a kind of intermezzo - a stage or activity in a process that stands alone and is not connected to the rest of the process. Because it has little or no connection to the process’s overarching objective, it is simply characterized by its appearance to the participants as out of context. On the other hand, it is anticipated that it will result in an increased level of energy as well as attention, which will positively impact the participants’ engagement and motivation as well as the remainder of the process.